Tumbuh Kembang Anak Usia SD Berdasarkan Fisik dan Mental - Kurniawan, Eka Yulayawan; Indriyani, Indriyani; Balqis, Luthfia (TSAQOFAH, 2024)
The age period between 6-12 years is a transition from pre-school to primary school (SD). This period is also known as the transition from early childhood to late childhood until just before pre-puberty. Physical growth develops rapidly and their health conditions improve. In addition to physical growth, there is also mental development of elementary school-age children that involves various important aspects affecting cognitive, emotional, and social development. The purpose of this article is to delve deeper into the Physical and Mental Development of Elementary School-Age Children. The type of research used in this study is a literature study (Library Research) with a qualitative research approach. The data collection technique used in this study is documentary study. The data sources used are books and journals related to the chosen topic. The data analysis used in this study is content analysis. The results obtained are the physical growth of elementary school-age children, namely a) the average during this period is 3-3.5 kg and 6 cm or 2.5 inches per year; b) head circumference grows only 2-3 cm during this period, indicating slow brain growth as the myelination process is complete at the age of 7 years; c) 6-year-old boys tend to weigh around 21 kg, approximately 1 kg heavier than girls. The mental development of elementary school-age children involves various important aspects that affect their cognitive, emotional, and social development. Piaget's cognitive development consists of several stages, namely: (1) Sensorimotor stage (0-2 years); (2) Preoperational (2-7 years); (3) Concrete operational (7-11 years); and (4) Formal operation (11-15 years). Emotional development is also very important in a child's development. This emotional development will go hand in hand with the child's social development.